Plan Estratégico para el desarrollo institucional del servicio nacional erradicación malaria (SNEM) en el cantón El Empalme periodo 2014-2018 - Bravo Medina, Wendy Yolanda (2014)
The Malaria is a parasitic disease caused by protozoa of the genus Plasmodium, transmitted by the bite of female Anopheles mosquitoes. Malaria in Ecuador 's health problems and a major cause of morbidity in the population living in areas at risk , affecting greatly to rural areas of the Coast and Amazon especially in the winter considered one of the largest Therefore the present study was mainly aimed at establishing a strategic plan for the institutional development of the National Service Malaria Eradication, targeting the population of El Empalme Canton, improve and implement new programs and projects to timely detect and control outbreaks epidemic malaria, and also to strengthen local capacity in terms of basic research, epidemiology, risk factors, ecological, social and economic determinants of the disease. That is why the development of this research inductive, logical methods applied - historical, analytic - synthetic and systemic , which provided an insight into the depth of investigation up to the Strategic Plan elaborates the institution ( SNEM ) for the period 2014-2018 . This project presents an investigation containing aspects of marked importance in achieving key derivation knowledge to a better development for optimization of resources embedded in the activities of SNEM. Within these tools and knowledge : The organization as an entity , concept and requirements for this exists, the organization as a system (open and closed) , organizational structure (organization ) , concept , purpose , leadership , organizational change and forces both internal and external influencing change management processes and phases that comprise the contingency theory of organization and the new strategy.